LELANG BARANG AGUNAN PERSPEKTIF HUKUM EKONOMI ISLAM - Asep Ridwan Hotoya (Mutawasith: Jurnal Hukum Islam, 2018)
The data used is primary data: interviews with respondents. Secondary Data is obtained from the library material. Analysis of qualitative analysis data with the intention of revealing the truth but understanding the truth. According to article 20 of the UUHT, the execution procedure of the rights of objects can only be done through 3 ways: (1) execution of parate (direct execution) (2) execution with the help of judges (3) execution of sales under hand. LAW No. 50/2009 Amendment of the second ACT No. 7/1989 on religious Judiciary article 54 mentions that 1rema of the event prevailing in the judiciary of religion is the same as the rema of the prevailing event in general justice, except for those things that have been specifically regulated in the LAW. In the deliberation of the judges suspending the auction of the execution of the object of liabilities: a plot of land and buildings attached thereon, SHM No. 1612/Cipedes A.N. Jayaningrat Nurlela, land area of 194 m² and building area of 125 m², located in Jalan Bojong Tengah No. 5, Cipedes village, Cipedes subdistrict, Tasikmalaya City and charge to Pelawan, opponent and opponent II to pay a case fee of Rp. 606,000 (six hundred six thousand Rupiah).